PENGARUH KEPERCAYAAN PADA PEMIMPIN DAN IMBALAN DAN UMPAN BALIK YANG SALING TERGANTUNG PADA BERBAGI PENGETAHUAN DENGAN TUJUAN PEMBELAJARAN TIM SEBAGAI MODERATOR: Studi Pada Tim Kreatif - , ERMITA; , Dr. Amin Wibowo, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study examines the determinants of knowledge sharing in the team creative of television and radio stations in Indonesia. We generated 233 questioners from 38 creative team. The data was analised using SPSS 17.0. There were four hypotheses proposed in this study, with two hypothesis were supported. Results indicated that trust in the leader positively affects the knowledge sharing. We found significant moderating effect of team learning goal towards the influence of trust in the leader on knowledge sharing. While, interdependent feedback and reward in influencing the knowledge sharing in team was not supported on data. The existence of team learning goal was found not significantly as a moderating variable towards the effect of trust in the leader on knowledge sharing. These findings confirm prior research and we discuss some findings specific to this study. Discussion and conclusion of this research produce some implications and further research is required on knowledge sharing in creative team.